Effect of adapter duration on repetition suppression in inferior temporal cortex - Pradeep Kuravi (Nature Portfolio, 2017)
Abstract Many inferior temporal (IT) cortical neurons reduce their response when a stimulus is repeated. Proposed mechanisms underlying this repetition suppression range from “fatigue” to top-down expectations of repetition. Here we examine a prediction from simple fatigue-based models of adaptation: prolonging adapter duration will increase the adapter response, leading to more repetition suppression. To test this, we varied adapter duration from 300 to 3000 ms, keeping the test stimulus duration constant. We observed no effect of adapter duration on repetition suppression when averaging responses across the test presentation. This was not because of a ceiling effect, since repeated presentations of a short adapter increased repetition suppression. Examination of test stimulus responses showed increased repetition suppression with longer adapter durations during the initial response phase, which reversed at a later phase. Across neurons, we found that the degree of repetition suppression covaried with the ratio of the response during the initial transient and later sustained phase of the response during the long adapter presentation, suggesting overlapping mechanisms that underlie adaptation during the adapter and the delayed test. We propose a fatigue-based account in which fatigue increases non-linearly with adapter duration to explain these unexpected findings.